Biomarkers in Nasopharyngeal Carcinoma (NPC): Clinical relevance and prognostic potential - Madhan Krishnan; Shyamaladevi Babu (Oral Oncology Reports)
Nasopharyngeal carcinoma (NPC) is a unique malignancy with a distinct epidemiological pattern, primarily affecting populations in Southeast Asia and Southern China. The identification and utilization of biomarkers in NPC have significantly advanced over recent years, offering promising avenues for improving clinical outcomes. Epstein-Barr virus (EBV) DNA remains the most widely recognized biomarker, playing a pivotal role in early detection, prognostic evaluation, and monitoring treatment responses. However, ongoing research has identified additional biomarkers, such as circulating tumor cells (CTCs), microRNAs, and immune-related molecules that provide further prognostic insights. These biomarkers not only enhance our understanding of NPC pathogenesis but also support personalized treatment approaches by stratifying patients based on risk and expected treatment outcomes. Clinically, the application of these biomarkers has the potential to transform NPC management, enabling more precise interventions and improving survival rates while minimizing treatment-related toxicity. The integration of these biomarkers into routine clinical practice could facilitate early diagnosis, predict therapeutic responses, and identify patients at higher risk of recurrence. Despite these advancements, further validation in large-scale clinical trials is required to fully realize their potential. This review discusses the clinical relevance and prognostic potential of established and emerging biomarkers in NPC, emphasizing their role in refining patient management and enhancing personalized therapeutic strategies. The continued exploration of these biomarkers holds promise for the development of novel diagnostic tools and treatment paradigms, ultimately improving outcomes for patients with NPC.